Game-specific characteristics of sport-related concussions - Helmich, I. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Concussions are common incidences in sports. However, game-specific characteristics such as tactics, field positions, etc. might positively/negatively contribute to the occurrence of mild traumatic brain injuries (mTBI) in various sports such as soccer, volleyball, handball, or basketball. Thus, the intention of this study was to analyze game-specific characteristics of concussive incidents in active players from the perspective of different sportive disciplines.